Heat transfer characteristics of supercritical water in a 2 × 2 rod bundle – numerical simulation and experimental validation. (5th May 2016) - Wang, Han; Bi, Qincheng; Wang, Linchuan
Highlights: Heat transfer of supercritical water in a 2 × 2 rod bundle is investigated. SSG Reynolds stress model agrees with the experimental data pretty well. Circumferential flow and heat transfer behaviors are illustrated. Conjugated heat transfer with pitch-to-diameter ratios is analyzed. Abstract: In this paper, heat transfer of supercritical pressure water in a 2 × 2 rod bundle was analyzed numerically. Three turbulence models were evaluated against experimental data. Comparisons showed that the SSG Reynolds stress model gives the best prediction for normal and enhanced heat transfer modes. Heat transfer of supercritical water in the rod bundle was studied with respect to the variations of mass flux, heat flux and pressure. Non-uniform distributions of bulk temperature exist on the cross-section of the flow channel, and the temperature gradient becomes small as the bulk temperature approaches the pseudo-critical temperature. Two heat generation methods from the rods, i.e. constant wall heat flux and internal heat source, were examined in the present analyses. Numerical results showed that the average heat transfer is nearly the same for the two methods, but the circumferential wall temperature gradient is significantly lowered when conjugate heat transfer is taken into consideration. The effects of pitch-to-diameter ratio (P/D) on heat transfer were also analyzed. Among the assessed four P/D ratios, the average heat transfer at the P/D of 1.2 is the best, and the circumferential wall temperature gradient is reduced with increasing P/D.